Pendapatan Nelayan Pencari Kepiting Bakau Di Desa Pasar Ngalam Kecamatan Air Periukan Kabupaten Seluma Propinsi Bengkulu - Rita Feni; Edy Marwan; Fithri Mufriantie; Sukardi Sukardi (Universitas Batangahari Jambi, 2021)
This study aims to determine whether or not the mangrove crab seeker business Desa Pasar Ngalam Kecamatan Air Periukan Kabupaten of Seluma regency is profitable. The method used in this research was the census, and questionnaire was used as instrument to retrieve data. On the other hand, 19 mangrove crabs seekers as respondents of the study. The results of analysis indicate that the average income earned by the mangrove crab seeker Desa Pasar Ngalam Kecamatan Air Periukan Kabupaten Seluma Regency is about Rp. 274.966, 20 per month